IKAFARSI BANJARMASIN PEDULI TERHADAP PENYAKIT TIDAK MENULAR MELALUI PENGABDIAN KEPADA MASYARAKAT - Herman Faisal; Aulia Rahim; Yugo Susanto (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
IKAFARSI ISFI Banjarmasin's concern for non-communicable diseases is implemented through the field of community service, namely the provision of free public health services for PTM by cooperating with STIKES ISFI Banjarmasin and BSMI South Kalimantan. This activity is in accordance with the Management Vision of IKAFARSI Banjarmasin for the 2023-2027 period, namely the creation of a connected, collaborative, and contributive IKAFARSI ISFI Banjarmasin with the mission of strengthening cooperation and contributions between alumni of STIKES ISFI BANJARMASIN in realizing the tridharma of higher education. The purpose of carrying out this community service is to increase public awareness about PTM and a healthy way of life. The implementation method used is face-to-face visitors directly express complaints with health workers, after they check their health then proceed with providing drug and health information. The results of the implementation of this community service were attended by 100 participants from Car Free Day (CFD) visitors at dr. Murdjani Banjarbaru, South Kalimantan, with details of 25 blood sugar checks, 25 uric acid checks, 20 cholesterol checks and 30 health consultations. The conclusion of the implementation of this activity is that public awareness of PTM is increasing and after providing drug and health information about PTM can increase public awareness for healthy living.